Untangling the additive and multiplicative relations between natural scenery exposure and human-animal interaction on affective well-being: Evidence from daily diary studies - GOH, Adalia Yin Hui (Institutional Knowledge at Singapore Management University, 2023)
Built nature spaces have been increasingly integrated into our urban environments in recent years with the aim of reaping their psychological benefits. However, despite numerous works of research on the relationship between nature exposure and well-being, most studies have looked into the benefits of well-being from the lens of isolated elements of nature, such as natural scenery or animal exposure. This study aims to fill in the gaps by examining the additive and multiplicative relationships between natural scenery exposure and human–animal interaction on affective well-being (i.e., positive affect, negative affect, and stress) through a daily diary study. Over seven days, natural scenery exposure, human–animal interactions, and affective well-being of 514 young adults were assessed. Through multilevel modelling, we found that natural scenery exposure was associated with increased positive affect at the within- and between-person levels. Moreover, human–animal interaction was associated with increased positive affect at the withinperson level. No evidence was found for human–animal interaction as a moderator of the relationship between natural scenery exposure and affective well-being. Our findings support the additive, but not multiplicative, relations between natural scenery exposure and human–animal interactions on their influence on affective well-being. The exploratory analysis showed the lack of multiplicative relationship which can be attributed to the distinct mechanism of the effect between natural scenery exposure and human–animal interactions on affective well-being.